PENGGUNAAN MEDIA PEMBELAJARAN COLOR PAPER UNTUK MENINGKATKAN MINAT DAN KETERAMPILAN MENULIS PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA - Ayu Sri Rahayu; Kuswara; Nia Royani (JESA-Jurnal Edukasi Sebelas April, 2024)
The background of this research is the low interest and early writing skills of students, especially in learning Indonesian. One of the factors that the reason why this happens is the lack of selection of learning media used to convey material that is still verbal. The problem that arises now is the low initial writing skills of students. Students tend to take for granted the material given by the teacher without responding in the form of opinions or rebuttals. To overcome this, researchers have a solution by applying color paper learning media. The purpose of this study was to describe the results of using color paper media in increasing students' interest and writing skills in starting students with living and non-living objects around me. Color paper media is a learning media made of paper that is attached with a sticky note which contains learning material. The research design used is the Kemmis and Mc Taggart spiral classroom action research (CAR) design. Based on the results of the study, it can be concluded that the color paper learning media can increase students' interest in learning and initial writing skills. It can be proven that the student's interest in learning has increased in each cycle. the results of the initial observation of the learning interest of grade I students at SD Negeri Bunter 1 in the Indonesian language subject with a total of 28 students, there were only 7 students in the "Good" category, 11 students in the "Enough" category, and 10 students in the "Less" category. With a class average of 57, the percentage of completeness is 25%, and the category "Less". In the first cycle of action, 28 students consisted of 14 students (50%) students who had achieved minimum completeness, 7 (25%) students who were categorized as sufficient, and 7 (25%) students who were categorized as having not achieved minimum completeness. And the average value of an interest in learning generated in the first cycle is 65 with a 50% completeness percentage in the "Enough" category. Then in the second cycle of 28 students consisting of 26 students. (93%) students have achieved minimum completeness. 2 (17%) students are categorized as moderate. And the average value of an interest in learning generated in the second cycle is 77 with a percentage of completeness of 93% and gets the criteria of "Good" this is due to the increased enthusiasm of students. It can be seen that the student's interest in learning has met the predetermined targets, namely good or very good criteria. In the results of students' initial writing skills, there was an increase in each cycle. The initial data obtained 32% with an average value of 67.6, the first cycle increased to 79% with an average value of 80, and the second cycle obtained 93 with an average value of 90. Based on the results of this study, it can be concluded that the learning media Color paper can improve students' interest and initial writing skills on living and non-living objects around me in grade I students at SD Negeri Bunter 1, Cimanggung District, Sumedang Regency, in the 2021/2022 academic year.